STRUCTURAL ANALYSIS OF IN-PLANE LOADED CLT BEAMS (Advances in Civil and Architectural Engineering, 2021)
Cross laminated timber (CLT) is a versatile engineered timber product that is increasingly well-known and of global interest in several applications such as full size plane or linear timber elements. The aim of this study involves investigating the performance of CLT beams loaded in-plane by considering bending and shear stress analysis with a special emphasis on the in-plane shear behavior including the complex internal structure of CLT. Numerical analysis based on 3D-FE models was used and compared with two existing analytical approaches, namely representative volume sub element (method I) and composite beam theory (method II). The separate verification of bending and shear stresses including tree different shear failure modes was performed, and a good agreement was obtained. The main difference between the results relates to shear failure mode in the crossing areas between the orthogonally bonded lamellas in which the distribution of shear stresses τzx over the crossing areas per height of the CLT beam is not in accordance with the analytical assumptions. The presented analyses constitute the first attempt to contribute to the on-going review process of Eurocode 5 with respect to CLT beams loaded-in plane. Currently, regulations on designing these types of beams do not exist, and thus experimental and numerical investigations are planned in the future.